Genetic analysis and validation of molecular markers associated with begomovirus resistance in chilli (Capsicum annuum L.) - Koka, Sai Timmarao; Ponnam, Naresh; D.C., Lakshmana Reddy; M., Krishna Reddy; V., Venkataravanappa; C.N., Hanchinamani; T.N., Lakshmidevamma; K., Madhavi Reddy (Journal of Horticultural Sciences, 2024)
Chilli is a crop of significant economic value, used as a vegetable cum spice. It has wide applications in the cosmeceutical, pharmaceutical, food and phyto feed industries. Chilli leaf curl disease (ChLCD) has become a major threat to crop production. Exploring host resistance is a sustainable approach to combating the viruses. In the present investigation, we studied the genetic inheritance of Chilli leaf curl virus in two resistant sources i.e. IHR4615 and IHR4597. The segregation ratios in the F2 populations indicated monogenic dominant gene governing the resistance. Further, the publicly available markers associated with begomoviruses resistance were screened in parents. pepy1 and Pepy2 genes resistance specific markers didn’t show any polymorphism among parents. PAU-LC-343-1 marker associated with Tomato leaf curl Joydebpur virus showed parental polymorphism, and its evaluation in the F2 population of IHR4615 × IHR2451 revealed that the marker is 40.16cM away from the resistance QTL governing ChLCV-Raichur isolate resistance, indicating both these loci are different. This marker can be explored for pyramiding resistant loci to develop broad spectrum resistance against begomoviruses in chilli.
Keywords: Chilli leaf curl virus; Chilli inheritance; Chilli resistance